W. E. B. Du Bois and the EVOLUTION OF 'RACE'. (2nd September 2022) - Shaw, Stephanie J.
Abstract: This essay situates the major works of W.E.B. Du Bois and some of his minor work between the 1880s and 1940 in the historical context of black people's writing about race since the eighteenth century. In offering examples of the evolution of black thinking and writing on this topic, it views Du Bois's work in the context of Moral and Ethical Philosophy (rather than the more obvious History, Sociology, and Political Economics) in order to reveal his efforts as a disruption, deliberately designed to shift the discussions of race and race relations from defense to offense, which he did most explicitly and profoundly in Dusk of Dawn (1940) but had been doing much more subtly throughout his scholarly career.